Modus operandi korupsi pada masa pertumbuhan pertambangan nikel di Sulawesi Tengah: Perspektif ‘Elite Capture’ (Integritas : Jurnal Antikorupsi, 2023)
This article aimed to explain the modus operandi of corrupt practices and identify potential state losses due to corruption in the nickel mining sector in Central Sulawesi. Elite capture theory, with a focus on the appropriation of natural resources by political and economic elites, was used as the analytical framework in this article. This study employed a qualitative-descriptive approach. The data was collected through literature and field studies. To identify the positions and relations of actors in the nickel mining business, the Social Network Analysis (SNA) method was used with the help of the Gephi software. This study found that the actors involved in the nickel mining business came from diverse backgrounds, including politicians, businessmen, bureaucrats, central government officials, regional officials, military personnel, and law enforcement officials. Network relations between actors were identified in five forms/patterns: business networks, family networks, party networks, government networks, and mass organization networks (social and religious). The modus operandi of actors and elites to obtain nickel mining concessions in Central Sulawesi was through land buying, selling and leasing, submitting legal opinions, buying and selling documents, rent extraction, shadow beneficial ownership, and illegal mining. Estimated potential state losses due to corruption in the mining sector since the growth of nickel in Central Sulawesi from 2011 to 2021 was estimated at approximately US$ 100 billion. As a novelty in literature, this research found that elite capture is not only realized through bribery (corruption) but also through intimidation and business cooperation.